Two new Neotropical genera of Miracinae (Hymenoptera, Braconidae) with unusual metasomal morphology - James B. Whitfield; Jose L. Fernandez-Triana; Caroline Boudreault (Journal of Hymenoptera Research)
Two morphologically unusual new neotropical genera of Miracinae, Paramomirax Whitfield and Fernandez-Triana, and Fusimirax Whitfield and Fernandez-Triana, are here proposed and described. The two new genera differ strikingly from previously known Miracinae in having completely different patterns of desclerotization of the anterior metasomal tergites. Paramomirax, so far known only from paramo vegetation at high elevation in Colombia, is represented by P. peckorum Whitfield, new species. Fusimirax, so far known only from lower elevation forests in the Dominican Republic, is described from three species, F. masneri Whitfield & Fernandez-Triana, new species, F. robusta Whitfield, new species, and F. gracilis, Whitfield, new species. None of the four species has any recorded hosts yet, although all previous Miracinae with known hosts attack leaf-mining and bark-mining moth larvae.